Enhancing Project Success: A Framework for PMO Maturity Assessment - Veronika, Alin (Avenew Indonesia, 2025)
Project Management Offices (PMOs) are critical for aligning projects with strategic goals. This white paper examines the importance of PMO maturity assessment, defining its benefits and exploring various assessment methodologies. We analyze prominent models, highlighting their strengths and weaknesses to guide organizations in selecting the most suitable approach for their context. We also present a case study illustrating the application of the PMO Maturity Cube within an Indonesian state-owned enterprise.